2004
DOI: 10.2298/gensr0403237s
|View full text |Cite
|
Sign up to set email alerts
|

Variability of dry substance accumulation and utilization parameters of Winter wheat plant

Abstract: Some dry substance accumulation and utilization parameters of wheat plant and their influence on grain yield have been studied through a field trial with 20 winter wheat cultivars. The studied parameters value (biological yield dry substance reutilization, number of grains per spike, 1000 grain mass plant height, etc) varried depending of genotypic specificity and environmental conditions. Grain yield was influenced not only by the total dry substance accumulation in plant (i.e. biological yield), but also by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The number of grains per spike ranged from 33.9 to 40.8 for different wheat varieties in Lloveras et al (2004) and the effects of variety, sowing density and year were significant at P ≤ 0.01, as well as their two-factor interactions. Stojković et al (2004), who investigated 20 winter wheat cultivars found that this parameter ranged from 37 to 54 in the first year, with average of 44 grains per spike and from 21 to 31 in the second year, with average of 26 grains per spike, while significant differences at both LSD levels for year and variety were present.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of grains per spike ranged from 33.9 to 40.8 for different wheat varieties in Lloveras et al (2004) and the effects of variety, sowing density and year were significant at P ≤ 0.01, as well as their two-factor interactions. Stojković et al (2004), who investigated 20 winter wheat cultivars found that this parameter ranged from 37 to 54 in the first year, with average of 44 grains per spike and from 21 to 31 in the second year, with average of 26 grains per spike, while significant differences at both LSD levels for year and variety were present.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies were done in order to investigate wheat spike parameters, such as number of grains per spike (Lloveras et al, 2004, Đurić et al, 2016, Stojković et al, 2004, Guberac et al, 2000, grain weight per spike (Knežević et al, 2015, Barić et al, 2008, Protić et al, 2013, Zečević et al, 2010, Gaile et al, 2017 and spike length (Banjac, et al, 2010;Kobiljski and Denčić, 1997;Shankarrao et al, 2010;Petrović et al, 2007;Zečević et al, 2004). It is also widely known that the obtained yield in specific environmental conditions is affected by the realization of yield components.…”
Section: Introductionmentioning
confidence: 99%